(untitled) (VERUM: Journal of Scientific Initiation, 2022)
This work aims to organize a brief exposition on the sociological treatment of education, as well as its aspects as a social dilemma and a factor of social change. In the first instance, we will base our analysis on the contributions of Florestan Fernandes and Karl Mannheim to define the object of this study. After that, we will focus on the discussion of the difficulties in interaction and the institutional role definition of each social actor involved in education. The goal of the presentation and theoretical analysis of this work is to contextualize and assist in the practical interpretation of the education dilemma as a social issue. However, the main objective is to shed light on the social influences of the families of students and the challenges faced by the entire school community regarding education, integration, and the delineation of roles involved in the development of the educational process. Once this foundation is laid, we plan to conduct an interview with teacher and researcher Iana Gomes de Lima, where we will address the new educational perspectives imposed by the coronavirus pandemic.